Optimasi Ukuran Lot Pemesanan Yang Ekonomis pada Permintaan Deterministik Dinamis Menggunakan Metode Heuristik Silver-Meal di PT. XYZ - Basuki . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
PT. XYZ is a automotive company with raw material ordered from a local company and imported. This study is focused on the imported components as the CKD (Completely Knock Down). Based on the data of December 2014 and January 2015, that the sale of PT. XYZ was not constant, but it fluctuatively per period. Problem was encountered on the phenomenon of dynamic demand is associated with determining operating stock and how to obtain a solution. The purpose of this study was to determine the economical lot size ordering and when to do a order. The Silver-Meal method was used to optimation order. Result from this study is that the economical lot size is equal to the number of demand and order which is done routinely in accordance with the lead time.